Dear Virginia, wait for me : a novel - Butler, Marcia (Central Avenue Publishing, 2025)
A sensitive portrait of a vulnerable yet resilient young woman who, with the help of an inner voice and newfound friends, attempts to find her way at the turn-of-the-millennium Manhattan. For as long as she can remember, Peppa Ryan has been guided by a benevolent voice in her head who she believes is Virginia Woolf. Though she's an exceptionally bright twenty-year-old, she suffers from crippling low self-esteem and has barely left her parents' ramshackle home in Queens, New York City. At the turn of the millennium, Peppa is caught between her father's wishes for her to run the family business and her mother's mental illness. In spite of these pressures, she bravely ventures out on her own to start a job at a Wall Street investment firm. But her parents continue to pull strings, insisting she date a handsome plumber in the hopes that she'll abandon her job and return to her roots. Peppa plans to immediately dismiss him, but to her surprise they discover an unlikely bond over a shared love of Virginia Woolf. With the encouragement of her kindhearted boss, his eccentric client, and the voice of Virginia, Peppa gains confidence and begins to thrive in her new life. Then, when Peppa discovers a betrayal by her family, she suffers a breakdown. And on one crisp and clear autumn morning, as she slowly recovers, Peppa finds herself on the path to reconciliation. For those who loved Where'd You Go, Bernadette, The Remedy for Love, or And Then We Came to The End, this is a sensitive coming-of-age novel of a fragile yet brilliant young woman who, like Virginia Woolf, is determined to carve her unique path in life.